When policymakers add administrative burdens while expanding access - Kyle, Jordan (Don Moynihan, 2023)
There is growing evidence that administrative burdens in social programs matter to access, and that we should do something about it. I’ve worked on such efforts in the federal government, helping to design revised guidance to the Paperwork Reduction Act to help to identify and reduce burdens. I’ve left the Office of Management and Budget now, but my time there and my academic research has given me new insights on the sources of administrative burdens, and some suggestions for how to reduce them. Administrative burdens in social safety net programs are often attributed to two main causes. First, they can arise from “benign neglect”: unwitting small decisions made early in program design that can have outsized effects on the populations the programs are intended to serve. In these cases, burdens flow from bureaucratic processes that are not themselves intended to harm the public—indeed, they are often designed to improve public administration—but end up resulting in onerous processes for individuals. Second, burdens arise from “hidden politics,” when paperwork and wait times are used to purposively limit access to public services. But there is an important third source of administrative burdens that’s not quite benign neglect or hidden politics: bureaucratic and legislative efforts to expand existing programs to cover new problems and new populations. Such efforts are benign but intentional, with the goal of broadening access rather than reducing it. We might think of this kind of institutional change as “layering;” essentially, adding new rules on top of existing ones.